(3YbhHI GdEYOGe aj VhA GdJTQjYGJ GdLfGFjI GdebGQfI (B/s - (3GdbGVj, JGeQ MGeO LGHQs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2017)
(3jbOe gPG GdcJGH OQGSI Mhd YbhHI GdEYOGe aj VhA GdJTQjYGJ GdLfGFjI GdebGQfI adG Tc Cf GdCfXeI GdYbGHjI GdJbdjOjI hGdeYGUQI MGaXJ Ydi eHOC GdJfGSH aj EjbGY GdYbhHI HGdfXQ Edi MLe GdLQe GdeQJcH aCbQJ CTO GdYbhHGJ Ydi CTO GdLQGFe hefgG YbhHI GdEYOGe GdJj HOhQgG YbhHI Jfgj MjGI GdLfGI hJXgQ CgejI gPg GdOQGSI GdfXQjI dGJSGegG HGdTehdjI MjK JfGhdJ GdJTQjYGJ GdYbGHjI hGdELQGFjI hGdbhGfjf GdecedI hGdNGUI aj GdJTQjYGJ GdebGQfI HGdTQM hGdJMdjd dQSe CaGb GdeSJbHd ddJTQjY ef NdGd ERGdI GdJfGbV hSO GdfbU GdPj TGH HYV GdfUhU JMbjbG dVHW CTO GdYbhHGJ LSGeI aj GdbGfhf GdLfGFj aYOGdI YbhHI GdEYOGe djSJ aj EbQGQgG hGfeG aj VHWgG hJfGSHgG eY GdLQe GdebJQa hTNUjI GdaGYd hShGHbg GdELQGejI(B. s
(3GdeMJhjGJ (B: (3GdebOeI(B-(3GdHGH GdJegjOj (B: (3PGJjI YbhHI GdEYOGe, GdaUd GdChd (B: (3eGgjI YbhHI GdEYOGe hNUGFUgG GdOGMVI deHQQGJ GdMedGJ GdefGgVI dgG, GdaUd GdKGfj (B: (3GdecGfI GdJGQjNjI dYbhHI GdEYOGe aj GdCfXeI GdLfGFjI GdebGQfI hJCUjdgG aj GdTQjYI GdESdGejI(B-(3GdHGH GdChd (B: (3GdCMcGe GdehVhYjI dYbhHI GdEYOGe aj GdJTQjYGJ GdLfGFjI GdebGQfI(B-(3GdHGH GdKGfj (B: (3GdCMcGe GdELQGFjI dYbhHI GdEYOGe aj GdJTQjYGJ GdYbGHjI GdebGQfI(B-(3GdNGJeI(B-(3bGFeI GdeQGLY GdYQHjI(B-(3agQS GdehVhYGJ(B. s
(3HHdjhLQGajI (B: (3UaMI (B679-731.s
Keywords: (3YbhHI GdEYOGes -- (3bhGfjf hJTQjYGJs -- (3adSWjfs; (3YbhHI GdEYOGe (B((3abg ESdGej(B)s; (3YbhHI GdEYOGes -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3YbhHI GdEYOGes -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdYbhHGJ GdLfGFjI s; (3GdbUGU s; (3GdEQgGHs; (3GdYUjGfs; (3GdJLSSs